THU0255 Chikungunya Fever in Patients Under Biologics Does not Seem to be Harmful. (9th June 2015) - Brunier, L.; Polomat, K.; Deligny, C.; Dehlinger, V.; Blettery, M.; Arfi, S.; Jean-Baptiste, G.; Blettery, M.; Debandt, M.
Abstract : Background: Chick is an epidemic disease due to an arthropod-borne virus ( Alphavirus ) transmitted by Aedes mosquitoes. CHIKV causes an acute illness with a febrile phase, followed by a period of severe polyarthritis that can persist for long time. There is no specific treatment, the best prevention is mosquito control and avoidance of bites. Martinique (French West Indies) is currently experiencing an outbreak of CHIK with 170 000 reported cases (Dec 1st). Objectives: No data is available regarding the prognosis of Chikungunya in patients under biologics. We have observed 22 patients with Chik infection while on biotherapy and DMARDS for rheumatic diseases, between January and May 2014. Methods: Physicians prescribing biologics were asked to declare patients under biologics experiencing Chik. For each patient we collected diseases characteristics and course, current treatment (steroids, immunosuppressant, biologics…), changes in the treatment during infection, and outcome. 22 patients were included, all with a diagnosis confirmed by PCR (20/22) or serology. Results: Among these patients were 19 women and 3 men, 3 Caucasians and 19 Afro-Caribbean's. There were 5 spondyloarthritis (3 associated with Crohn), 1 psoriatic rheumatism, 2 systemic lupus, 1 antisynthetase syndrome and 13 RA. 17 had methotrexate (mean dose 21.6 mg), 3 Plaquenil, 2 Imuran, 1 cellcept, 2 cyclophosphamide. 11/22 were under steroids (mean dose of 8.6 mg/d). All experienced fever (mean duration 1.7 day), skin rash (15/22, mean duration 1.3 d), and acute disabling polyarthritis (mean pain VAS 8.4, mean SJC 9.6, mean TJC 6.8) for a mean 11.5 days duration. Nine had back pain and 4 tenosynovitis. None of them showed any organ failure, one single episode of transient thrombopenia was noted. None of them was hospitalized for Chik. Analgesic treatment (alone 4/22), associated with NSAIDs (17/22) or prednisone (1/22) and rest were sufficient to overcome the crisis. All but one patient maintained their previous treatment (DMARDS, Biologic, steroids…) without specific complication. All patients were able to differentiate between Chik related complains and those related to their preexisting condition. Mean clinical disease scores before and after Chik (DAS, BASDAI, SLEDAI) remained unchanged. Conclusions: This is the first report of the occurrence of Chik in patients under biologics. Patients under biologics are at increased risk for serious infections either viral or bacterial, but no data has been published regarding Chik. This study was not conducted to discover all cases of Chik among patients under biologic. Chik does not seem to be deleterious in patients under biologics who do not exhibit more severe or prolonged disease than common forms. Chik does not seem to aggravate pre-existing disease. It does not seem necessary to modify the basic treatment of rheumatism in the announcement of a Chik as the clinical pictures observed in these patients are quite benign. NSAIDs and best rest are mostly effective. Chik does not seem harmful in patients receiving biological and this issue should be given to travellers. Disclosure of Interest: None declared